Relationship between organic agriculture and export of olive oil in Tunisia via an ARDL model - Jeder, Houcine (Food, Agriculture and Natural Resources - NETWORKS, 2023)
This paper aims to study the presence of the relationship between the organic olive-growing area and the export of olive oil in the Tunisian economy; such as the producer price index for the case of olives and the exchange rate. A cointegration approach through an Auto Regressive Distributed Lag model (ARDL model) was mobilized for the period (2001-2021). The test results show the existence of a significant short and long-terms cointegration relationship between the olive area, the exchange rate and the export of olive oil. Similarly, unidirectional causal relationships have also been determined between the producer price index and the olive area on the one hand, a unidirectional causal relationship is caused by the exchange rate on the olive-growing area and this exerts unidirectional causality on the export of olive oil. The promotion of organic farming in Tunisia depends not only on the development of organic areas but also on the economic situation of the country. Thus, it can be concluded that limiting the depreciation of the national currency and improving the producer price index can improve the exchange rate and contribute positively to the development of organic olive areas and the export of olive oil in general